2018
DOI: 10.1038/s41433-018-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy training in England: are we safe at training? Two year surgical outcomes

Abstract: The outcomes of supervised trainee trabeculectomy compare favourably with consultant cases after 2 year follow up. Trainee cases had higher complication rates than consultant cases. Bleb leaks are a common complication of trainee cases, where closer supervision may be required. There is potential for surgical simulation to help increase the success of such cases. These findings may encourage trainee participation in glaucoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…One of the largest studies of trainee surgery from the UK analysed over three hundred cases, and found supervised trainee trabeculectomy outcomes to compare favourably with those of consultants in terms of qualified and unqualified success rates. 13 Of note, trainee outcomes were similar to those reported in large national landmark studies. 11,12 Other studies from the UK and the US reinforce the notion that acceptable supervised trainee surgical outcomes can be achieved.…”
Section: Trainee Trabeculectomy Outcomessupporting
confidence: 68%
See 3 more Smart Citations
“…One of the largest studies of trainee surgery from the UK analysed over three hundred cases, and found supervised trainee trabeculectomy outcomes to compare favourably with those of consultants in terms of qualified and unqualified success rates. 13 Of note, trainee outcomes were similar to those reported in large national landmark studies. 11,12 Other studies from the UK and the US reinforce the notion that acceptable supervised trainee surgical outcomes can be achieved.…”
Section: Trainee Trabeculectomy Outcomessupporting
confidence: 68%
“…5,[14][15][16][17] As would be expected, trainee groups have been reported to have significantly higher complication rates when compared with consultant cases, with bleb leaks and hypotony being the most frequent complications. 13,15 Bleb closure and suturing techniques have therefore been suggested as an area to be specifically targeted in terms of improving trainee outcomes, echoing previous suggestions from the literature that this may be a result of suturing skills being encountered less frequently in modern surgical training. 5,13,15 It is difficult to directly compare the outcomes of these studies as different definitions of success are used in conjunction with varying lengths of follow up data and trainee surgical experience.…”
Section: Trainee Trabeculectomy Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the cases in fellowship as a trainee are closely supervised by senior glaucoma surgeons and hence not a true reflection of the complications we face as a new independent surgeon. Walkden et al 30 found no significant difference in success rates between consultant and supervised trainee trabeculectomy surgeries. However, trainees had higher complication rates with bleb leaks being common, an indication that closer supervision may be required.…”
Section: Discussionmentioning
confidence: 96%